1995
DOI: 10.1016/0092-8674(95)90120-5
|View full text |Cite
|
Sign up to set email alerts
|

Rabaptin-5 is a direct effector of the small GTPase Rab5 in endocytic membrane fusion

Abstract: We have identified a novel 100 kDa coiled-coil protein, rabaptin-5, that specifically interacts with the GTP form of the small GTPase Rab5, a potent regulator of endocytic transport. It is mainly cytosolic, but a fraction colocalizes with Rab5 to early endosomes. Expression of a GTPase-deficient Rab5 mutant enhances the binding of rabaptin-5 to enlarged endosomes. Overexpression of rabaptin-5 alone is sufficient to promote expansion of early endosomes. Rab5 recruits rabaptin-5 to purified early endosomes in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
426
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 449 publications
(452 citation statements)
references
References 55 publications
21
426
1
4
Order By: Relevance
“…Initially, rabaptin-5 was identified as an interactor of rab5 (Stenmark et al, 1995) and rabex-5 as a rab5 guanine nucleotide exchange factor (Horiuchi et al, 1997). Rabaptin-5 in addition was shown to bind to rab4 and AP-1 (Vitale et al, 1998;de Renzis et al, 2002;Deneka et al, 2003).…”
Section: Rab4 and Rabaptin-5/rabex-5 Regulate The Formation Of Recyclmentioning
confidence: 99%
“…Initially, rabaptin-5 was identified as an interactor of rab5 (Stenmark et al, 1995) and rabex-5 as a rab5 guanine nucleotide exchange factor (Horiuchi et al, 1997). Rabaptin-5 in addition was shown to bind to rab4 and AP-1 (Vitale et al, 1998;de Renzis et al, 2002;Deneka et al, 2003).…”
Section: Rab4 and Rabaptin-5/rabex-5 Regulate The Formation Of Recyclmentioning
confidence: 99%
“…The domain can be recognized in five proteins from baker's yeast, Saccharomyces cerevisiae, and in several mammalian proteins including early endosomal autoantigen 1 (EEA1), Hrs, and SARA (Smad anchor for receptor activation) (30,38). In yeast, three of these proteins have been implicated in the regulation of endocytic trafficking events (Vps27, Fab1, and Vac1 [4]), while in mammalian cells EEA1 has been shown to regulate early endosome fusion (16,27).…”
mentioning
confidence: 99%
“…Rab5 also regulates the homotypic fusion of early endosomes. Rabaptin-5, EEA1, hVPS34/p150, and Rabenosyn-5 have been identified as Rab5 target proteins (Stenmark et al, 1995;Christoforidis et al, 1999aChristoforidis et al, , 1999bCallaghan et al, 1999). The characterization of these target proteins has revealed that Rab5 can regulate several steps through these multiple target proteins and that these target proteins act cooperatively to coordinate the various functions of Rab5 in early endocytic traffic.…”
Section: Introductionmentioning
confidence: 99%